POWER LOSSES ANALYSIS IN 3 PHASE DISTRIBUTION TRANSFORMER IN NORMAL LOAD AND OVER LOAD CONDITION USING ARTIFICIAL NEURAL NETWORKS TECHNIQUE - Suechoey, Boonlert; Siriporananon, Somsak (Srinakharinwirot University Journal of Sciences and Technology, 2023)
This research paper presents power loss analysis in a 3-phase distribution transformer of 100 kVA 22 kV-230/400 V in normal load and overload conditions using a neural network technique. This method can analyze power loss in the transformer quicker and use fewer variables than the power loss calculation using various parameters obtained from transformer manufacturers. Seventy thousand sets of current tests ranging from 1% - 140% at temperatures of 35oC, 45oC, 55oC, 65oC and 75oC were experimentally measured, then power losses are calculated. Fifty-six thousand sets of those were used for training of the neural network to find the parameters and the other 14,000 sets were used for the input data to find power losses. In addition, the power losses ​​obtained from the artificial neural network were compared with calculated power losses by using parameters from transformer manufacturers. The error percentage value no more than 1.06 was at a satisfactory level suggestingthat this method can be applied in the designing of electrical power loss test for transformers in the future.